Plataforma Eletrônica para Aquisição de Sinais Fisiológicos de Bovinos a Pasto - RICARDO ESPINDOLA DE AGUIAR (2022)
The animal production global market is increasingly demanding, including sustainability and animal welfare requirements. Physiological changes such as increased heart rate or body temperature may show poor welfare or even characterize pre-pathological health state. This work focuses on the development of a animal's monitoring platform. The platform has a non-invasive device (sensor and electronic circuits set) to collect photopletismografic signals and skin temperature and ultraviolet radiation data. After collecting the physiological signals, digital signal filters are applied to extract out noises. The filtered data are sent to a base station and then to a cloud platform where algorithms for heart beat and respiratory rates estimates are applied on the data. Experiments were designed so that the platform was evaluated on animals under different sensor positions (neck, forehead, and nape) and animal's conditions. The experiments show that the signals are improved after applying the filtering algorithms. Another interesting finding is that the nape neck has shown to be a suitable position to collect physiologic (photopletismografic) signals and to keep the electronic platform for long-run and non-invasive experiments.